2018
DOI: 10.1186/s13075-018-1748-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatitis B virus surface antibody titer and risk of hepatitis B reactivation in HBsAg-negative/HBcAb-positive patients undergoing biologic therapy for rheumatic diseases: a prospective cohort study

Abstract: BackgroundOur aim was to investigate dynamic changes in hepatitis B virus (HBV) surface antibody (HBsAb) titer and the associated risk of HBV reactivation and clinical course in patients with HBV surface antigen negative/core antibody positive (HBsAg−/HBcAb+) serostatus during antirheumatic therapy with biologic agents.MethodsIn a prospective study from January 2013 to June 2017, we monitored the HBV serostatus of HBsAg−/HBcAb+ patients undergoing biologic therapy for rheumatic diseases. From HBsAb titers at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 22 publications
5
49
2
4
Order By: Relevance
“…In our study, HBV reactivation occurred approximately 3.5 years after the initiation of RTX therapy and a mean of 6 months after the last RTX dose. A previous study in Taiwan showed a mean time to HBV reactivation of approximately 2 years from the first dose of RTX 29 . The differences in these results may be related to the monitoring protocol.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, HBV reactivation occurred approximately 3.5 years after the initiation of RTX therapy and a mean of 6 months after the last RTX dose. A previous study in Taiwan showed a mean time to HBV reactivation of approximately 2 years from the first dose of RTX 29 . The differences in these results may be related to the monitoring protocol.…”
Section: Discussionmentioning
confidence: 95%
“…There were no HBVr cases in the 'high' group, whereas cases of transient HBV viremia were seen in the both the 'low' (2.5/100 person-years) and 'negative' group (4.7/100 person-years). 106 Among 1042 Japanese patients with rheumatic diseases and resolved HBV infection who received both conventional and biological treatments, HBVr incidence was overall low (1.93/100 person-years), but increased to 4.32/100 person-years in anti-HBc positive/ anti-HBs negative patients. The risk ratios for HBVr were 2.8 and 3.1 for anti-HBs titres below the median (71.4 IU/mL) and the cut-off for detection (<10 IU/mL), respectively.…”
Section: Rtx and Other B-mentioning
confidence: 99%
“…The ability of the body to protect itself from infection or immunity [10] can be acquired artificially through vaccination) or naturally after recovery from infection. In both scenarios, the individual develops anti-hepatitis B surface antibodies, but these should exceed 10 mlU/mL for them to be protected from infec- [11]. This study was designed to determine the prevalence of viral Hepatitis B among pregnant women, classify whether the infection was acute or chronic, determine whether the pregnant women were infectious or not and to evaluate immunity among those who were HBV negative.…”
Section: Infectiousness Of Hepatitis B or Risk Of Transmission Dependmentioning
confidence: 99%
“…The findings of a high rate of transmission have implications, especially given the role of Hepatitis B in the causa-tion of Cancer of the liver. Suffice to note that HBV integrates and persists for life in the hepatocyte nuclei as covalently closed circular DNA (cccDNA) [4] thus the virus may reactivate when HBsAb levels reduce [11]; moreover the integrated virus accelerates procarcinogenic events that trigger hepatocyte turnover [3] and may lead to cancer of the liver. Our findings are different from what was observed among Health Care Workers (HCWs) in Indonesia where 18.5% had natural immunity and 36% had artificial immunity [20].…”
Section: Evaluation Of Immunitymentioning
confidence: 99%